Short-term effects of air pollution on respiratory morbidity at Rio de Janeiro - Part II: Health assessment - S. I. V. Sousa (2012)
The effects of air pollution on health have been studied worldwide. Given that air pollution triggers oxidative stress and inflammation, it is plausible that high levels of air pollutants cause higher number of hospitalisations. This study aimed to assess the impact of air pollution on the emergency hospitalisation for respiratory disease in Rio de Janeiro, Brazil. The study was divided in two parts: Part I specifically addressing the air pollution assessment and Part II addressing the health assessment. Accordingly, this Part II aimed to estimate the association between the concentrations of PM10, SO2 and CO observed in Rio de Janeiro and the number of emergency hospitalisations at a central hospital due to respiratory diseases. The pollutant concentrations were measured at two different sites in Rio de Janeiro, but the excess relative risks were calculated based on the concentrations observed at one of the sites, where limits were generally exceeded more frequently, between September 2000 and December 2005. A time series analysis was performed using the number of hospitalisations, divided in three categories (children until 1 year old, children aged between 1 and 5 years old and elderly with 65 years old or more) as independent variable, the concentrations of pollutants as dependent variables and temperature, relative humidity, long term trend, and seasonality as confounders. Data were analysed using generalised additive models with smoothing for some of the dependent variables. Results showed an excess risk of hospitalisation for respiratory disease higher than 2% per 10 mu g m(-3) increase in PM10 concentrations for children under 5 years old, of 2% per 10 mu g m(-3) increase in SO2 for elderly above 65 years old and around 0.1% per 10 mu g m(-3) increase in CO for children under 1 year and elderly. Other studies have found associations that are in agreement with the results achieved in this study. The study suggests that the ambient levels of air pollutants experienced in Rio de Janeiro between 2000 and 2005 were linked to the number of hospitalisations for respiratory diseases among children and elderly.